2015
DOI: 10.1186/s13104-015-1347-x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in non-diabetic patients with unstable angina/non ST-segment elevation myocardial infarction

Abstract: BackgroundMicroalbuminuria (MAU) is defined as an urinary albumin excretion rate between 20–200 mg/l or 30–300 mg/day. It is a surrogate marker for endothelial dysfunction and is independently associated with atherosclerotis in diabetic and in non-diabetic patients. We assessed the prevalence of MAU in non-diabetic patients who presented with UA/NSTEMI and the relation of MAU to the severity of coronary artery disease in patients at a cardiac care center in Iraq.MethodsSeventy non-diabetic patients referred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 34 publications
2
16
0
7
Order By: Relevance
“…The current study showed that patients with MAU have a greater atherosclerotic burden and a more severe CAD in the form of total number of vessels affected per patient than those without MAU. The results are in accordance with the previously reported findings [ 19 - 22 ]. In the present study, presence of MAU exhibited a significant correlation with the severity of CAD (r = 0.094; P < 0.001).…”
Section: Discussionsupporting
confidence: 94%
“…The current study showed that patients with MAU have a greater atherosclerotic burden and a more severe CAD in the form of total number of vessels affected per patient than those without MAU. The results are in accordance with the previously reported findings [ 19 - 22 ]. In the present study, presence of MAU exhibited a significant correlation with the severity of CAD (r = 0.094; P < 0.001).…”
Section: Discussionsupporting
confidence: 94%
“…15 Hilal Bahjet AL-Saffar, Hussein Nassir et al suggested that patients with UA/ NSTEMI found a strong correlation of microalbuminuria with echo-graphic changes and findings in coronary angiography. 16 Male 42 43 85 Female 08 07 15 Total 50 50 100 Table- The result of our study indicates that there is highly significant microalbuminuriain non-diabetic,nonhypertensive AMI patients. The level of significance (P< 0.001) of microalbuminuria in our study, was comparable to that observed, in other international study.…”
Section: Discussionmentioning
confidence: 67%
“…Zeeshan A, Ahmad Z, Tahir GA, Yaqoob Y in their study on acute coronary syndrome titled MA as atherosclerotic risk factors and its association found MA in 20.4% cases of STEMI. The corresponding figures in NSTEMI and Unstable angina were 21.3% and 25.3% respectively 15 . In contrast, Abdul Ghaffar Memon and Mubashir Kolachi in their study on relationship of MA in non-diabetic and non-hypertensive patients with acute myocardial infarction done in Hyderabad, Pakistan found MA in 53.17% STEMI and15.8% NSTEMI 8 .…”
Section: Discussionmentioning
confidence: 94%
“…ST segment elevation MI cases were not included in their study 14 . Association of microalbuminuria with dyslipidemia and obesity was not significant in our study; however few studies have shown significant association 6,[15][16][17][18] . 98 out of 100 ACS patients in our study were having one or more risk factors.…”
mentioning
confidence: 99%